Protection of the Civilian Population in the Times of Armed Conflicts and Natural Disasters. Case study of a medium-sized town - Okrzesik, Janusz (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
The paper discusses the level of preparedness for the protection of civilians during armed conflicts and natural disasters. The author describes the Polish civil defence system on the example of a medium-sized town - Bielsko-Biała. The paper begins with the presentation of the legal status of civil protection in Poland. Next the paper looks at the personal and material resources of the system as well as the organizational structure of civil defence in the town of Bielsko-Biala. In the conclusion of the paper, the author assesses the level of preparedness of the local administration to respond to a serious crisis. The conclusions of this assessment are very critical.